La libertad religiosa en Estados Unidos: Una perspectiva internacional - John Witte, Jr. (Universidad Hemisferios, 2019)
This Article compares United States religious freedom jurisprudence with prevailing international human rights norms. I distill these international religious freedom norms and evaluate how selected US Supreme Court cases both follow and depart from these norms. Part I identifies six principles of religious freedom defended by the American framers who crafted the First Amendment in 1791: liberty of conscience; free exercise of religion; religious pluralism; religious equality; separation of church and state; and no establishment of religion. Part II summarizes the mostly parallel norms of religious freedom in the 1966 International Covenant on Civil and Political Rights, the 1981 UN Declaration on the Elimination of All Forms of Intolerance and Discrimination Based on Religion or Belief, and the 1989 Vienna Concluding Document. Part III shows how the US Court’s cases on freedom of conscience, free exercise, and religious equality compare favorably to international standards, although some religious minorities have often not fared well. Some of the Court’s cases defending the principle of separation of church and state mesh well with international concerns for religious autonomy. But the Court’s establishment clause cases have gone well beyond international norms in expunging religion from public schools and removing state aid for religious groups and services. The Article concludes that religious freedom remains a strong constitutional value in American law and culture, but it needs to be better integrated; international religious freedom norms offer valuable lessons to that end.